Benefits of counting blessings in basic psychological needs satisfaction and subjective well-being of prisoners - Peng, Jiaxi (Psychology, crime & law, 2022)
Counting blessings is one of the gratitude intervention methods to promote gratitude and subjective well-being (SWB). This study aimed to examine whether counting blessings could effectively promote SWB in prisoners and test whether the effect was mediated by gratitude and satisfaction of basic psychological needs (BPN). A total of 124 male prisoners wrote either grateful things or a control topic. The results demonstrated that counting blessings were associated with significant increase in gratitude, partially increases in satisfaction of BPN, and slightly increase SWB at the post-intervention assessment. Additionally, gratitude and satisfaction of BPN mediated the effect of counting blessings on SWB.